Analisis Rasio Keuangan Sebagai Dasar dalam Menilai Kinerja Keuangan Rumah Sakit Ibu dan Anak Paradise Tanah Bumbu Periode Tahun 2018-2022 - Ayu Niken Faizati; Sri Bulkia; Noorlaily Maulida; Sanusi Sanusi (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
Several studies on hospital financial performance show that financial success is an important metric for measuring the performance of private hospitals during the COVID-19 pandemic. Analyzing hospital financial reports can be done to evaluate financial performance. Financial ratio analysis was chosen as a method for assessing financial performance because of the diversity of aspects that can be measured, such as liquidity, profitability, profitability and operational activities. Through this analysis, it will be possible to understand how the financial performance of Paradise Mother and Child Hospital has changed during the 2018-2022 period, including in the context of the pandemic. Thus, this study is expected to provide valuable insights for hospital management and other stakeholders in facing future challenges. The results of the study show: (1) In terms of Liquidity Ratio ( Current Ratio and Quick Ratio ), RSIA Paradise's liquidity performance declined significantly in the 2018-2020 period, with the lowest point in 2020 due to the COVID-19 pandemic. Although there was a recovery in 2021 and 2022. (2) Based on the solvency ratio, RSIA Paradise shows that the company experienced an increase in dependence on debt during the 2018-2020 period, with a significant increase in 2020 due to the impact of the COVID-19 pandemic. (3) Based on the performance of RSIA Paradise activities, it shows that the efficiency of the use of fixed assets and total assets fluctuated during the 2018-2022 period. (4) Based on the profitability performance ratio, RSIA Paradise showed significant fluctuations during the 2018-2022 period.